Download Inverse Trigonometric Functions

Survey
yes no Was this document useful for you?
   Thank you for your participation!

* Your assessment is very important for improving the work of artificial intelligence, which forms the content of this project

Transcript
Section 3.5 Inverse Trigonometric Functions
2010 Kiryl Tsishchanka
Inverse Trigonometric Functions
DEFINITION: The inverse sine function, denoted by sin−1 x (or arcsin x), is defined to be
the inverse of the restricted sine function
π
π
sin x, − ≤ x ≤
2
2
DEFINITION: The inverse cosine function, denoted by cos−1 x (or arccos x), is defined to
be the inverse of the restricted cosine function
cos x, 0 ≤ x ≤ π
DEFINITION: The inverse tangent function, denoted by tan−1 x (or arctan x), is defined
to be the inverse of the restricted tangent function
π
π
tan x, − < x <
2
2
DEFINITION: The inverse cotangent function, denoted by cot−1 x (or arccot x), is defined
to be the inverse of the restricted cotangent function
cot x, 0 < x < π
1
Section 3.5 Inverse Trigonometric Functions
2010 Kiryl Tsishchanka
DEFINITION: The inverse secant function, denoted by sec−1 x (or arcsec x), is defined to
be the inverse of the restricted secant function
[
]
sec x, x ∈ [0, π/2) ∪ [π, 3π/2) or x ∈ [0, π/2) ∪ (π/2, π] in some other textbooks
DEFINITION: The inverse cosecant function, denoted by csc−1 x (or arccsc x), is defined
to be the inverse of the restricted cosecant function
[
]
csc x, x ∈ (0, π/2] ∪ (π, 3π/2] or x ∈ [−π/2, 0) ∪ (0, π/2] in some other textbooks
IMPORTANT: Do not confuse
sin−1 x,
with
cos−1 x,
1
,
sin x
1
,
cos x
tan−1 x,
cot−1 x,
1
,
tan x
1
,
cot x
FUNCTION
DOMAIN
−1
sin x
[−1, 1]
cos−1 x
[−1, 1]
−1
tan x
(−∞, +∞)
−1
cot x
(−∞, +∞)
−1
sec x
(−∞, −1] ∪ [1, +∞)
csc−1 x
(−∞, −1] ∪ [1, +∞)
2
sec−1 x,
1
,
sec x
csc−1 x
1
csc x
RANGE
[−π/2, π/2]
[0, π]
(−π/2, π/2)
(0, π)
[0, π/2) ∪ [π, 3π/2)
(0, π/2] ∪ (π, 3π/2]
Section 3.5 Inverse Trigonometric Functions
FUNCTION
sin−1 x
cos−1 x
tan−1 x
cot−1 x
sec−1 x
csc−1 x
2010 Kiryl Tsishchanka
DOMAIN
RANGE
[−1, 1]
[−π/2, π/2]
[−1, 1]
[0, π]
(−∞, +∞)
(−π/2, π/2)
(−∞, +∞)
(0, π)
(−∞, −1] ∪ [1, +∞) [0, π/2) ∪ [π, 3π/2)
(−∞, −1] ∪ [1, +∞) (0, π/2] ∪ (π, 3π/2]
sin(−x) = − sin x
cos(−x) = cos x
tan(−x) = − tan x
csc(−x) = − csc x
sec(−x) = sec x
cot(−x) = − cot x
sin(x ± π) = − sin x
cos(x ± π) = − cos x
tan(x ± π) = tan x
sec(x ± π) = − sec x
csc(x ± π) = − csc x
cot(x ± π) = cot x
EXAMPLES:
(a) sin−1 1 =
π
π
π [ π π]
, since sin = 1 and ∈ − , .
2
2
2
2 2
( π)
π [ π π]
π
= −1 and − ∈ − , .
(b) sin−1 (−1) = − , since sin −
2
2
2
2 2
[ π π]
(c) sin−1 0 = 0, since sin 0 = 0 and 0 ∈ − , .
2 2
(d) sin−1
1
π
π
1
π [ π π]
= , since sin = and ∈ − , .
2
6
6
2
6
2 2
√
3
π
π
3
π [ π π]
= , since sin =
and ∈ − , .
2
3
3
2
3
2 2
√
(e) sin
−1
√
(f) sin
−1
√
2
π
π
2
π [ π π]
= , since sin =
and ∈ − , .
2
4
4
2
4
2 2
EXAMPLES:
π
cos−1 0 = ,
2
tan−1 1 =
π
,
4
cos−1 1 = 0,
cos−1 (−1) = π,
π
tan−1 (−1) = − ,
4
tan−1
√
cos−1
3=
π
,
3
tan−1
EXAMPLES: Find sec−1 1, sec−1 (−1), and sec−1 (−2).
3
√
3
π
2
π
cos−1
= , cos−1
=
2
6
2
4
(
)
1
π
1
π
√ = , tan−1 − √
=−
6
6
3
3
π
1
= ,
2
3
√
Section 3.5 Inverse Trigonometric Functions
FUNCTION
sin−1 x
cos−1 x
tan−1 x
cot−1 x
sec−1 x
csc−1 x
2010 Kiryl Tsishchanka
DOMAIN
RANGE
[−1, 1]
[−π/2, π/2]
[−1, 1]
[0, π]
(−∞, +∞)
(−π/2, π/2)
(−∞, +∞)
(0, π)
(−∞, −1] ∪ [1, +∞) [0, π/2) ∪ [π, 3π/2)
(−∞, −1] ∪ [1, +∞) (0, π/2] ∪ (π, 3π/2]
sin(−x) = − sin x
cos(−x) = cos x
tan(−x) = − tan x
csc(−x) = − csc x
sec(−x) = sec x
cot(−x) = − cot x
sin(x ± π) = − sin x
cos(x ± π) = − cos x
tan(x ± π) = tan x
sec(x ± π) = − sec x
csc(x ± π) = − csc x
cot(x ± π) = cot x
EXAMPLES: Find sec−1 1, sec−1 (−1), and sec−1 (−2).
Solution: We have
sec−1 1 = 0,
sec−1 (−1) = π,
sec−1 (−2) =
since
sec 0 = 1,
and
sec π = −1,
sec
4π
3
4π
= −2
3
4π [ π ) [ 3π )
0, π,
∈ 0,
∪ π,
3
2
2
Note that sec
2π
is also −2, but
3
sec−1 (−2) 6=
since
2π
3
2π [ π ) [ 3π )
6∈ 0,
∪ π,
3
2
2
EXAMPLES: Find
tan−1 0
cot−1 0
cot−1 1
sec−1
4
√
2
csc−1 2
2
csc−1 √
3
Section 3.5 Inverse Trigonometric Functions
2010 Kiryl Tsishchanka
EXAMPLES: We have
tan−1 0 = 0,
cot−1 0 =
π
,
2
cot−1 1 =
π
,
4
sec−1
√
2=
π
,
4
csc−1 2 =
π
,
6
2
π
csc−1 √ =
3
3
(
)
( π)
8π
π)
EXAMPLES: Evaluate sin arcsin
, arcsin sin
, and arcsin sin
.
7
7
7
(
Solution: Since arcsin x is the inverse of the restricted sine function, we have
sin(arcsin x) = x if x ∈ [−1, 1]
(
π) π
sin arcsin
=
7
7
Therefore
but
arcsin(sin x) = x if x ∈ [−π/2, π/2]
and
(
8π
arcsin sin
7
)
(
π) π
arcsin sin
=
7
7
and
( (π
))
(
( π)
π)
π
= arcsin sin
+π
= arcsin − sin
= − arcsin sin
=−
7
7
7
7
(
2
EXAMPLES: Evaluate cot arcsin
5
)
(
2
and sec arcsin
5
)
.
Solution 1: We have
√
cos θ
± 1 − sin2 θ
cot θ =
=
sin θ
sin θ
Since −
sec θ =
1
1
= √
cos θ
± 1 − sin2 θ
π
π
2
≤ arcsin x ≤ , it follows that cos(arcsin x) ≥ 0. Therefore if θ = arcsin , then
2
2
5
√
1 − sin2 θ
1
cot θ =
and sec θ = √
sin θ
1 − sin2 θ
√
hence
(
2
cot arcsin
5
and
and
(
2
sec arcsin
5
(
2
1 − sin2 arcsin
5
(
)
2
sin arcsin
5
)
=
)
=√
1 − sin2
1
(
√
)
=
( )2
2
1−
√
5
21
=
2
2
5
5
1
)=√
( )2 = √21
2
2
arcsin
1−
5
5
2
2
Solution 2: Put θ = arcsin , so sin θ = . Then
5
5
√
(
(
)
)
2
21
2
5
cot arcsin
and sec arcsin
= cot θ =
= sec θ = √
5
2
5
21
(
)
EXAMPLES: Evaluate, if possible, cot sin−1 2 and sin (tan−1 2) .
5
!
5 !!!
!
!!
!
!! θ √
21
2
Section 3.5 Inverse Trigonometric Functions
2010 Kiryl Tsishchanka
(
)
EXAMPLES: Evaluate, if possible, cot sin−1 2 and sin (tan−1 2) .
We first note that sin−1
does
( 2 −1
) not exist, since 2 6∈ [−1, 1], that is, 2 is not in the domain of
−1
sin x. Therefore cot sin 2 does not exist.
We will evaluate sin (tan−1 2) in two different ways:
Solution 1: We have
tan θ
sin θ = ± √
1 + tan2 θ
Since −π/2 < tan−1 x < π/2, it follows that cos (tan−1 x) > 0. Therefore if θ = tan−1 2, then
sin θ = √
hence
tan θ
1 + tan2 θ
(
)
tan (tan−1 2)
2
2
√
√
sin tan−1 2 = √
=
=
1 + 22
5
1 + tan2 (tan−1 2)
Solution 2: Put θ = tan−1 2 = tan−1
5
θ
√
2
2
, so tan θ = . Then
1
1
(
)
2
sin tan−1 2 = sin θ = √
5
(
EXAMPLES: Evaluate sin cot−1
(
1
−
2
))
(
and cos cot−1
6
(
1
1
−
2
))
.
2
Section 3.5 Inverse Trigonometric Functions
2010 Kiryl Tsishchanka
(
(
−1
EXAMPLES: Evaluate sin cot
1
−
2
))
(
(
−1
and cos cot
1
−
2
))
.
Solution 1: We have
sin θ = ± √
−1
Since 0 < cot
1 + cot2 θ
x < π, it follows that sin(cot
(
(
−1
sin cot
and
and
−1
sin θ = √
hence
1
1
−
2
1
1 + cot2 θ
=√
(
1
1 + cot2 θ
cos θ = √
(
1
2
1
−
2
)
, then
cot θ
1 + cot2 θ
)) = √
(
1
(
1+ −
2
)2 = √ 5
1
2
))
1
1
(
( ))
cot cot
−
−
1
1
2
2
cos cot−1 −
=√
=√
= −√
(
(
))
(
)
2
2
5
1
1
1 + cot2 cot−1 −
1+ −
2
2
−1
(
−1
Solution 2: Put θ = cot
and
(
−1
1 + cot2 cot−1 −
(
cot θ
x) > 0. Therefore if θ = cot
and
))
cos θ = ± √
)
1
−1
, so cot θ = − =
. Then
2
2
(
( ))
1
2
−1
sin cot
−
= sin θ = √
2
5
1
−
2
(
(
−1
cos cot
A
A
2
1
−
2
))
1
= cos θ = − √
5
A
A
A
A
A
A
A √
A 5
A
A
A
A
A
A
A
-1
7
Aθ
Section 3.5 Inverse Trigonometric Functions
2010 Kiryl Tsishchanka
THEOREM: We have
(a) (sin−1 u)0 = √
1
u0
1 − u2
(b) (cos−1 u)0 = − √
(c) (tan−1 u)0 =
(d) (cot−1 u)0 = −
1
u0
2
1−u
1
u0
1 + u2
1
(e) (sec−1 u)0 = √
u0
2
u u −1
1
u0
1 + u2
1
(csc−1 u)0 = − √
u0
2
u u −1
(f)
Proof:
(a) Let y = sin−1 u, then sin y = u. Therefore
0
(sin y) = u
Since −
0
0
cos y · y = u
=⇒
0
u0
y =
cos y
0
=⇒
π
π
−1
≤ sin
u} ≤ , it follows that cos y ≥ 0. Hence
|
{z
2
2
y
√
cos y =
1 − sin2 y = [sin y = u] =
√
1 − u2
y0 =
=⇒
u0
u0
=√
cos y
1 − u2
(b) Let y = cos−1 u, then cos y = u. Therefore
(cos y)0 = u0
=⇒
− sin y · y 0 = u0
=⇒
y0 = −
u0
sin y
−1
Since 0 ≤ cos
| {z u} ≤ π, it follows that sin y ≥ 0. Hence
y
sin y =
√
1 − cos2 y = [cos y = u] =
√
1 − u2
=⇒
y0 = −
u0
u0
= −√
sin y
1 − u2
(c) Let y = tan−1 u, then tan y = u. Therefore
(tan y)0 = u0
=⇒
sec2 y · y 0 = u0
=⇒
Note, that sec2 y = 1 + tan2 y = [tan y = u] = 1 + u2 . Hence
y0 =
u0
u0
=
sec2 y
1 + u2
8
y0 =
u0
sec2 y
Section 3.5 Inverse Trigonometric Functions
(a) (sin−1 u)0 = √
1
u0
2
1−u
(b) (cos−1 u)0 = − √
(c) (tan−1 u)0 =
2010 Kiryl Tsishchanka
(d) (cot−1 u)0 = −
1
u0
2
1−u
1
u0
2
1+u
1
(e) (sec−1 u)0 = √
u0
2
u u −1
1
u0
1 + u2
(f)
1
(csc−1 u)0 = − √
u0
u u2 − 1
(d) Let y = cot−1 u, then cot y = u. Therefore
(cot y)0 = u0
=⇒
− csc2 y · y 0 = u0
=⇒
y0 = −
u0
csc2 y
Note, that csc2 y = 1 + cot2 y = [cot y = u] = 1 + u2 . Hence
y0 = −
u0
u0
=
−
csc2 y
1 + u2
(e) Let y = sec−1 u, then sec y = u. Therefore
(sec y)0 = u0
sec y tan y · y 0 = u0
=⇒
=⇒
y0 =
u0
sec y tan y
−1
Since sec
| {z u} ∈ [0, π/2) ∪ [π, 3π/2), it follows that tan y ≥ 0. Hence
y
√
√
sec y tan y = sec y sec2 y − 1 = [sec y = u] = u u2 − 1
=⇒
u0
u0
√
y =
=
sec y tan y
u u2 − 1
0
(f) Let y = csc−1 u, then csc y = u. Therefore
(csc y)0 = u0
=⇒
− csc y cot y · y 0 = u0
=⇒
y0 = −
u0
csc y cot y
−1
Since csc
| {z u} ∈ (0, π/2] ∪ (π, 3π/2], it follows that cot y ≥ 0. Hence
y
√
√
csc y cot y = csc y csc2 y − 1 = [csc y = u] = u u2 − 1
EXAMPLES:
(a) Let f (x) = x tan−1 (1 − 2x). Find f 0 (x).
(b) Let f (x) = 2sin
(c) Let f (x) =
√
−1 (4x)
. Find f 0 (x).
sec−1 (1 − 3x). Find f 0 (x).
9
=⇒
u0
u0
√
y =−
=−
csc y cot y
u u2 − 1
0
Section 3.5 Inverse Trigonometric Functions
(a) (sin−1 u)0 = √
1
u0
1 − u2
(b) (cos−1 u)0 = − √
(c) (tan−1 u)0 =
2010 Kiryl Tsishchanka
(d) (cot−1 u)0 = −
1
u0
1 + u2
1
(e) (sec−1 u)0 = √
u0
2
u u −1
1
u0
2
1−u
1
u0
1 + u2
1
(csc−1 u)0 = − √
u0
2
u u −1
(f)
EXAMPLES:
(a) Let f (x) = x tan−1 (1 − 2x). Then
f 0 (x) = [x tan−1 (1 − 2x)]0 = x0 tan−1 (1 − 2x) + x[tan−1 (1 − 2x)]0
= 1 · tan−1 (1 − 2x) + x
= tan−1 (1 − 2x) + x
1
· (1 − 2x)0
2
1 + (1 − 2x)
1
· (−2)
1 + (1 − 2x)2
2x
1 + (1 − 2x)2
x
= tan−1 (1 − 2x) −
1 − 2x + 2x2
= tan−1 (1 − 2x) −
(b) Let f (x) = 2sin
−1 (4x)
. Then
[
]0
[
]0
−1
−1
f 0 (x) = 2sin (4x)
= 2sin (4x) ln 2 · sin−1 (4x)
= 2sin
= 2sin
−1 (4x)
−1 (4x)
ln 2 √
ln 2 √
−1 (4x)+2
2sin
= √
(c) Let f (x) =
√
1
1 − (4x)2
1
1 − (4x)2
· (4x)0
·4
ln 2
1 − (4x)2
sec−1 (1 − 3x). Then
1
f 0 (x) = [(sec−1 (1 − 3x))1/2 ]0 = (sec−1 (1 − 3x))−1/2 · [sec−1 (1 − 3x)]0
2
1
1
√
= (sec−1 (1 − 3x))−1/2
· (1 − 3x)0
2
2
(1 − 3x) (1 − 3x) − 1
1
1
√
· (−3)
= (sec−1 (1 − 3x))−1/2
2
(1 − 3x) (1 − 3x)2 − 1
=−
3
√
2(1 − 3x) 3x(3x − 2) sec−1 (1 − 3x)
10
Document related concepts
no text concepts found
Similar